Added sensitivity of component‐resolved diagnosis in hymenoptera venom‐allergic patients with elevated serum tryptase and/or mastocytosis. Issue 5 (23rd February 2016) - Michel, J.; Brockow, K.; Darsow, U.; Ring, J.; Schmidt‐Weber, C. B.; Grunwald, T.; Blank, S.; Ollert, M.
Abstract: Background: Anaphylaxis caused by hymenoptera venom allergy is associated with elevation of baseline serum tryptase (sBT) and/or mastocytosis in about 5% of patients. Up to now, no information has become available on single venom allergen sIgE reactivity and the usefulness of component‐resolved approaches to diagnose this high‐risk patient group. To address the component‐resolved sIgE sensitization pattern and diagnostic sensitivity in hymenoptera venom‐allergic patients with elevated sBT levels and/or mastocytosis, a panel of yellow jacket and honeybee venom allergens was applied on a widely used IgE immunoassay platform. Methods: Fifty‐three patients with mastocytosis and/or elevated sBT tryptase level and systemic reactions to hymenoptera venoms were analyzed for their IgE reactivity to recombinant yellow jacket and honeybee venom allergens by Immulite3 g. Results: sIgE reactivity to Ves v 1, Ves v 5, Api m 1 to Api m 4 and Api m 10 was found at a similar frequency in hymenoptera venom‐allergic patients with and without elevated sBT levels and/or mastocytosis. However, the use of the recombinant allergens and a diagnostic cutoff of 0.1 kUA /L allowed the diagnosis of patients with otherwise undetectable IgE to venom extract. The diagnostic sensitivity of yellow jacket venom allergy using the combination of Ves v 1 and Ves v 5 was 100%. Conclusions: In high‐risk patients with elevated sBT levels and/or mastocytosis, the use of molecular components and decreasing the threshold sIgE level to 0.1 kUA /L may be needed to avoid otherwise undetectable IgE to hymenoptera venom extracts in about 8% of such patients.